Nanostructured Silver Thin Film: Using Successive Ionic Layer Adsorption and Reduction Method - Yatem, Ari A.; Rammoo, Mohammed S. (Science Journal of University of Zakho, 2023)
The Successive Ionic Layer Adsorption and Reduction (SILAR) method was utilized to produce nanostructured silver thin films on a glass substrate. Ag nanoparticles were grown using SILAR parameters such as silver nitrate (AgNO3), reduction time, reduction agent in an aqueous solution of hydrazine hydrate with various concentrations, and growth cycles. In this study, X-ray diffraction (XRD), scanning electron microscopy (SEM), and UV-visible-NIR absorption spectroscopy techniques were used to assess the produced silver thin film nanostructure. The size and spreading of the formed silver nanoparticles are observed to grow with the reducing agent and eventually saturate for constant growth cycles. As a result, the size and the distribution of the produced Ag nanoparticles grow uniformly. Higher growth cycles, however, caused Ag nanoparticles to lose their homogeneity and change into gravel-shaped particles. Therefore, silver nanoparticles that have been produced with the ideal SILAR conditions can be employed as an extremely sensitive, repeatable substrate with an exceptionally efficient factor. Moreover, the Effect of the concentration of HyH on the properties of SILAR-grown silver thin films has been extensively studied.